2013
DOI: 10.5539/jedp.v3n1p222
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety, Optimism and Academic Achievement among Students of Private Medical and Engineering Colleges: A Comparative Study

Abstract: Courses related to medical and engineering fields are quite extensive and demanding, which often lead to stress and anxiety among students. As optimism was hypothesized to reduce anxiety and enhance academic achievement, the purpose of the current study was to assess the level of anxiety and its relation with optimism and academic achievement among medical and engineering students. Since these two courses differ in many aspects and the gender roles in the society are changing, the secondary objective of the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
3
11

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(79 citation statements)
references
References 65 publications
(46 reference statements)
2
54
3
11
Order By: Relevance
“…Several studies have found negative relationships between optimism and anxiety (Bagana, Raciu, & Lupu, 2011;I. Singh & Jha, 2013), and negative emotionality (S. E. Taylor & Armor, 1996), which can be considered components of the doubtfulness style.…”
Section: Aim Of the Studymentioning
confidence: 99%
“…Several studies have found negative relationships between optimism and anxiety (Bagana, Raciu, & Lupu, 2011;I. Singh & Jha, 2013), and negative emotionality (S. E. Taylor & Armor, 1996), which can be considered components of the doubtfulness style.…”
Section: Aim Of the Studymentioning
confidence: 99%
“…For example, optimists has linked to higher levels of engagement of coping and lower levels of avoidance, taking proactive steps to protect one's health, relates to benefits in the socioeconomic world, more persistence in educational efforts and to higher later income, fare better in relationships. Evidence came from coping styles in stress also found out those optimisms tend to adopt problem-focused coping strategies, whereas pessimists tend to avoid directly confronting the problem itself and use emotion-focused ones (Singh and Jha 2013;Jobin et al 2013).…”
Section: Introductionmentioning
confidence: 98%
“…Oleh karena itu, Singh (2013) menyimpulkan bahwa mahasiswa kedokteran memiliki tingkat ansietas, depresi, serta stres yang lebih tinggi dibandingkan populasi umum pada kelompok usia yang sama. 4 Pada tingkat akhir pre-klinik (tingkat empat) S1 Kedokteran, mahasiswa juga diwajibkan mengerjakan skripsi atau tugas akhir sehingga mahasiswa tingkat akhir akan mengalami ansietas walaupun sudah beradaptasi dengan lingkungan perkuliahan. Skripsi menjadi ketakutan bagi mahasiswa tingkat akhir karena membuat skripsi bukanlah hal yang mudah serta skripsi juga dibuat saat mahasiswa sedang menjalani blok seperti biasa, sehingga pikiran mahasiswa harus terbagi antara skripsi dan blok yang harus dijalani.…”
Section: Pendahuluanunclassified